Dançando no escuro: um método de ensino das atividades rítmicas e expressivas para pessoas com deficiência visual - Lopes, Súsel Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Physical education is the responsible area of knowledge of the manifestations of body culture (sports, dances, gymnastics, plays, wrestles, among others). Among them, the rhythmic and expressive movement activities, which offer a very broad possibility of work of adapted physical education. Due to the refinement of body movements, the improvement of the notion of spatial localization and social interaction, which are proven to be provided by inclusive rhythmic and expressive movement activities. It was observed by private interest, a good opportunity for the development of a research aimed at the visually impaired public. With the aim of stimulating emotional, mental and physical gains, providing stimuli that improves self-confidence, satisfaction, rhythm, and displacement, using plays and body culture games. To guide this research, an evolutionary teaching methodology was developed. Idealized from gymnastic movements, fundamentals of contemporary dance, music therapy, art therapy and reports of situations experienced by people with visual impairment. The participants of the research were users from the Lar Escola Santa Luzia para Cegos, 13 people with visual impairment (low vision/blind), both sexes, adults and elderly (20-96 years), sedentary, and interested in physical activity. Bringing a proposal of activities with rhythmic-sensorial exercises, to improve/extend motor skills, with audio descriptive-oriented body practices and other perceptual sensory stimuli. There was a need for the creation of assistive technologies to collaborate in the execution of the gymnastic activities/plays and the displacement on the stage... (Complete abstract electronic acess below)

A educação física é a área responsável pelo conhecimento das manifestações da cultura corporal (esportes, danças, ginásticas, jogos, lutas, entre outras). Dentre elas, as atividades rítmicas e expressivas, que oferecem uma possibilidade bastante ampla de trabalho da educação física adaptada. Devido ao refinamento dos movimentos corporais, da melhora da noção de localização espacial e da interação social, que são comprovadamente proporcionadas pelas atividades rítmicas e expressivas inclusivas. Foi observada por interesse particular, uma boa oportunidade para o desenvolvimento de uma pesquisa voltada para o público deficiente visual. Com o objetivo de estimular ganhos emocionais, mentais e físicos, proporcionando estímulos que melhorem a autoconfiança, a satisfação, o ritmo, e o deslocamento, usando jogos e brincadeiras da cultura corporal. Para nortear esta pesquisa, foi elaborada uma metodologia de ensino evolutiva. Idealizada a partir de movimentos gímnicos, fundamentos da dança contemporânea, musicoterapia, arterapia e de relatos de situações vividas por pessoas com deficiência visual. Participaram da pesquisa os usuários do Lar Escola Santa Luzia para Cegos, sendo 17 pessoas com deficiência visual (baixa visão/cegos), ambos os sexos, adultos e idosos (20-96 anos), sedentários, com interesse em atividade física. Trazendo uma proposta de atividades com exercícios rítmico-sensoriais, para melhorar/ampliar as habilidades motoras, com práticas corporais orientadas por audiodescrição e outros estímulos sensoriais perceptivos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação física para deficientes; Distúrbios da visão; Dança - Bauru (SP); Dance - Brazil